CARTILAGE-ON-CARTILAGE VS. METAL-ON-CARTILAGE IMPACT CHARACTERISTICS AND RESPONSES - Heiner, Anneliese D. (2013)
A common in vitro model for studying acute mechanical damage in cartilage is to impact an isolated osteochondral or cartilage specimen with a metallic impactor. The mechanics of a cartilage-on-cartilage (COC) impact, as encountered in vivo, are likely different than those of a metal-on-cartilage (MOC) impact. The hypothesis of this study was that impacted in vitro COC and MOC specimens would differ in their impact behavior, mechanical properties, chondrocyte viability, cell metabolism, and histologic structural damage. Osteochondral specimens were impacted with either an osteochondral plug or a metallic cylinder at the same delivered impact energy per unit area, and processed after 14 days in culture. The COC impacts resulted in about half of the impact maximum stress and a quarter of the impact maximum stress rate of change, as compared to the MOC impacts. The impacted COC specimens had smaller changes in mechanical properties, smaller decreases in chondrocyte viability, higher total proteoglycan content, and less histologic structural damage, as compared to the impacted MOC specimens. If metal-on-cartilage impact conditions are to be used for modeling of articular injuries and post-traumatic osteoarthritis, the differences between COC and MOC impacts must be kept in mind.